Principio pattizio e garanzia dell’eguaglianza tra le confessioni religiose: il punto di vista della Consulta nella sentenza n. 52 del 2016 (Stato, Chiese e pluralismo confessionale, 2017)
Il contributo, sottoposto a valutazione, è destinato alla pubblicazione nel volume a cura di M. Parisi, Bilateralità pattizia e diritto comune dei culti. A proposito della sentenza n. 52/2016, Editoriale Scientifica, Napoli, 2017.SOMMARIO: 1. Introduzione - 2. L’attuazione del principio pattizio tra esigenze politiche del Governo e tutela giurisdizionale dei diritti - 3. Diniego di avvio delle trattative, qualificazione religiosa dei soggetti istanti e uguale libertà: i nodi problematici e le soluzioni.ABSTRACT: The judgment no. 52/16 of the Constitutional Court has related to a conflict of powers between branches of State, in particular between the Council of Ministers and the Supreme Court, canceling the judgment of the Supreme Court (judgment no. 16305, June 28, 2013) with which it was established the syndicatability to the courts of the government resolution which had been denied to the Union of Atheists and Rationalist Agnostics the opening of negotiations for the signing of the agreement, in accordance with Article 8, third paragraph, of the Constitution. In reaching that conclusion, the Constitutional Court considered necessary some considerations relating to the nature and the meaning that, in our constitutional system, assume the agreement for the regulation of relations between the state and the non-Catholic religious denominations. At the same time, the Judge of the Laws has also been called upon to interpret the first paragraph of Article 8, which, in stating that all religions are equally free before the law, exclude that the State can foster the expansion of a religious group compared to the others.